2017
DOI: 10.1016/j.jpainsymman.2016.12.330
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Tools in Patients With Advanced Cancer: A Systematic Review

Abstract: Various prognostic tools have been validated but vary in their complexity, subjectivity, and therefore clinical utility. The Glasgow Prognostic Score would seem the most favorable as it uses only two parameters (both objective) and has prognostic value complementary to the gold standard measure, which is performance status. Further studies comparing all proved prognostic markers in a single cohort of patients with advanced cancer are needed to determine the optimal prognostic tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
156
2
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 60 publications
4
156
2
12
Order By: Relevance
“…The PPSv2 is a modified version of the Karnofsky performance scale and is used to measure functional status in palliative care 11,12 and predict survival among terminally ill patients. The PPSv2 is a modified version of the Karnofsky performance scale and is used to measure functional status in palliative care 11,12 and predict survival among terminally ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…The PPSv2 is a modified version of the Karnofsky performance scale and is used to measure functional status in palliative care 11,12 and predict survival among terminally ill patients. The PPSv2 is a modified version of the Karnofsky performance scale and is used to measure functional status in palliative care 11,12 and predict survival among terminally ill patients.…”
Section: Introductionmentioning
confidence: 99%
“…Simmons et al . recently reviewed the role of prognostic models in advanced cancer [12]. They concluded that ‘various prognostic tools have been validated, but vary in their complexity, subjectivity and therefore clinical utility’ [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although this review is unable to provide evidence of causation it is important for healthcare professionals to be aware of these prognostic factors and their incorporation into existing prognostic models [12], which may be useful in clinical practice. However, further research is needed to understand the application of biomarkers in prognostication at the end of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Systemic inflammation is an important determinant of disease progression and survival in patients with cancer, [14] and various prognostic scores incorporating routine measures of the systemic inflammatory response have been proposed for use in advanced cancer. [15,16] One such score, the modified Glasgow Prognostic Score (mGPS), is based on the combination of serum C-reactive protein (CRP) and albumin concentrations and has been shown to hold prognostic value not only across several solid organ cancers, but also across patients undergoing treatment with both curative and palliative intent. [17,18] As such, the systemic inflammatory response, and the mGPS appears a rational and easily measurable characteristic on which to base a prognostic scoring system for patients with advanced OG cancer.…”
Section: Introductionmentioning
confidence: 99%